Socio-demographic and economic determinants of adherence to iron intake among pregnant women in selected low and lower middle income countries in Asia: insights from a cross-country analyses of global demographic and health surveys - Warvadekar, Kirti; Reddy, J. C.; Sharma, Sona; Dearden, Kirk A.; Raut, Manoj Kumar (International Journal Of Community Medicine And Public Health, 2018)
Background: Anaemia is a global public health problem affecting around 800 million children and women worldwide. Anaemia, defined as a reduced haemoglobin concentration, is associated with increased peri-natal mortality, increased child morbidity and mortality, impaired mental development, impaired immune competence, increased susceptibility to lead poisoning, and decreased performance at work. Methods: This paper attempts to understand the determinants underlying iron intake in select countries in Asia using multivariate regression analyses of recent data from the Demographic and Health Surveys of eight countries of Afghanistan, Cambodia, India, Indonesia, Myanmar, Nepal, Pakistan, and the Philippines. The individual level data was analysed, using Predictive Analytics Software for Windows (PASW) 18.0 release. Results: After adjusting for standard co-variates, exposure to newspaper was found to be associated with increased adherence to iron tablets or syrup, in five of the eight countries (India, Indonesia, Nepal, Pakistan, and the Philippines). Exposure to television was significantly associated with coverage and adherence to iron tablets or syrup in Afghanistan, India, Indonesia and Myanmar. Those who received at least three antenatal care visits were much more likely to adhere to at least 90 days of iron tablet or syrup or iron and folic acid tablets supplementation. Conclusions: Based on insights from eight demographic and health surveys, mass media (including print and TV), as well as antenatal care-seeking visits seem to be a particularly effective ways of reaching women and in increasing the likelihood of uptake of iron only or iron and folic acid supplements.